Kendalikan Gaya Hidup: Literasi Keuangan Untuk Pengguna Pay Later - Casmini; Muhammad Bayu Irfan Pratama (UIN Sunan Kalijaga, 2026)
Abstract - Recent activities in Batuan Village, Bali, highlight the importance of financial literacy in managing consumer behavior, particularly regarding